The reaction of perfluoroglutaric acid with methyl magnesium iodide. Part 2 - Smith, D. A. (College of Aeronautics, 1968)
Perfluoroglutaric acid when treated with methyl magnesium iodide afforded hexafluoro-2,6-dimethylpyran-2,6-diol in high yield and 2,213,3,4,4-hexafluoro- 5-oxocaproic acid in low yield. The former appeared to exist in a range melting form (61.-79°C) and also in a very labile form melting at 96-98°C. Problems associated with the formation of this latter form were investigated. The hexafluoro-2,6-dimethylpyran-2,6-diol yielded a monosemi-carbazone and also a mono and a di1(2,4-dinitrophenylhydrazone). The mono (2,4-dinitro phenylhydrazone) appeared to be cyclic. Reduction, both with lithium aluminium hydride and sodium borohydride yielded 3,3,4,415,5-hexafluoro-n-heptane-2,6-diol. Reaction with anhydrous calcium sulphate gave 3,3,414,515-hexafluoro-2- methylcyclohex-l-ene-6-one. The acid product of the original reaction of perfluoroglutaric acid and methyl magnesium iodide was characterised as a 2,4-dinitrophenylhydrazone and as an S-benzylthiouronium salt. Infra-red spectroscopic evidence suggests the latter compound exists in a straight chain form.